The fertility of buffalo sperm (Bubalus bubalis) on three diluent types and three equilibration times - -, Yendraliza; Handoko, Jully; Rodiallah, Muhammad; Arman, Chairusyuhur (Buffalo Bulletin, 2022)
This study objective was to determine the fertility of buffalo sperm in response to different types of diluent and equilibration times. The first research stage was arranged in completely randomized design with two factors, i.e., diluent types (tris egg yolk, andromed, and triladyl) and equilibration times (3 h, 4 h and 5 h). The second research stage was the fertility test of frozen semen that artificialy inseminated on 90 4-years-old buffalo-cows. The observed variables were the percentage of motility, abnormality, membrane plasma integrity, acrosome intact, recovery rate and pregnancy rate. The result showed that there was no interaction between diluent types and equilibration times on all observed variables. The best buffalo sperm fertility was produced from andromed and tris egg yolk compared to triladlil diluent. The best equilibration time for buffalo semen was 5 h rather than 4 h and 3 h.